Planning With Patient-Specific Rectal Sub-Region Constraints Decreases Probability of Toxicity in Prostate Cancer Radiotherapy - Lafond, Caroline; Barateau, Anaïs; N'Guessan, Joël; Perichon, Nicolas; Delaby, Nolwenn; Simon, Antoine; Haigron, Pascal; Mylona, Eugenia; Acosta, Oscar; de Crevoisier, Renaud (Frontiers in Oncology, 2020)
Background A rectal subregion (SRR) has been previously identified by voxel-wise analysis in the inferior-anterior part of the rectum as highly predictive of rectal bleeding in prostate cancer radiotherapy. Translating the SRR to patient-specific radiotherapy planning is challenging as new constraints have to be defined. A recent geometry-based model proposed to optimize the planning by determining the achievable mean doses (AMD) to the organs at risk (OAR), taking into account the overlap between the PTV and OAR. The aim of this study was to quantify the SRR dose sparing by using the AMD model in the planning, while preserving the dose to the prostate. Material and methods 3D VMAT Planning dose distributions for 60 patients were computed following four different strategies, delivering 78 Gy to the prostate, while meeting the genitourinary group (GETUG) dose constraints to the OAR: i) A standard plan corresponding to the standard practice for rectum sparing (STDpl), ii) a plan adding constraints to SRR (SRRpl), iii) a plan using the AMD model applied to the rectum only (AMD_RECTpl) and iv) a final plan using the AMD model applied to both the rectum and the SRR (AMD_RECT_SRRpl). After PTV dose normalization, plans were compared with regards to dose distributions, quality and estimated risk of rectal bleeding using a NTCP model. Results AMD_RECT_SRRpl showed the largest SRR dose sparing, with significant mean dose reductions of 7.7 Gy, 3 Gy and 2.3 Gy, with respect to the STDpl, SRRpl and AMD_RECTpl, respectively. AMD_RECT_SRRpl also decreased the mean rectal dose by 3.6 Gy relative to STDpl and by 3.3 Gy relative to SRRpl. The absolute risk of grade ≥ 1 rectal bleeding decreased from 22.8% using STDpl planning to 17.6% using AMD_RECT_SRRpl considering SRR volume. AMD_RECT_SRRpl plans showed however slightly less dose homogeneity and significant increase of the number of monitor units, compared to the three other strategies. Conclusion Compared to a standard prostate planning, applying dose constraints to a patient-specific SRR by using the achievable mean dose model decreased the mean dose by 7.7 Gy to the SRR and may decrease the relative risk of rectal bleeding by 22%.